A Study of Out-of-Band Emission in Digital Transmitters Due to PLL Phase Noise, Circuit Non-Linearity, and Bandwidth Limitation - Mohammad Oveisi; Seyedali Hosseinisangchi; Payam Heydari (IEEE Open Journal of Circuits and Systems, 2023)
A thorough investigation of major contributors to out-of-band emission (OOBE) in transmitters (TXs) utilizing digital modulation schemes is provided. Specifically, the paper delves into the detrimental effects of phase noise of the local oscillator (LO), typically realized using a phase-locked loop (PLL), on the OOBE phenomenon. Furthermore, the effects of the circuit nonlinearity in a TX, widely recognized as a primary contributor to spectral regrowth and elevated levels of OOBE, are investigated. Additionally, the impact of filtering and bandwidth (BW) limitation on OOBE is taken into account. Comprehensive simulations verify the accuracy of the analytical study. The results provided throughout this paper can be used to determine the linearity and phase noise requirements of different blocks, such as PLL and power amplifier (PA) within a TX chain to design a system complying with a specific mask emission dictated by a particular standard.